Association Study of rs1421085 and rs9939609 in FTO Gene with Gestational Diabetes in the Arak City - Parnian Hekmatpou; Maryam Maryam Ghanbari; Milad Gholami (Majallah-i dānishgāh-i ̒ulūm-i pizishkī-i Arāk)
Introduction: Gestational diabetes is defined as hyperglycemia with onset or first diagnosis during pregnancy, with a lower frequency than general diabetes. Overweight and obesity, old age at the time of pregnancy, previous history of gestational diabetes, family history of type 2 diabetes, and race are risk factors for gestational diabetes. Recently, the relationship between two polymorphisms (rs9939609 and rs1421085) of Fat mass and obesity-associated (FTO) gene and the risk of gestational diabetes has been investigated in some studies with conflicting results. Therefore, our aim of the present study was to investigate the association study of rs1421085 and rs9939609 of the FTO gene on gestational diabetes. Methods: In this case-control study, five cc of peripheral blood was collected from 100 cases with gestational diabetes and 116 control pregnant women from Taleghani Hospital in Arak, and then DNA was extracted. After designing the specific primers, the genotypes were determined by the Tetra ARMS-PCR method. Demographic information was compared with genotypes between the two groups were compared using SNPSTAT software. Results: A significant correlation was observed between obesity, BMI before and during pregnancy, HbA1c, FBS, cholesterol, and triglyceride levels among mothers with gestational diabetes compared to healthy pregnant mothers P = 0.0001. According to data analysis, there was no significant association between rs1421085 and rs9939609 of the FTO gene with gestational diabetes. Conclusions: Considering the conflicting results between the association of FTO gene polymorphisms with gestational diabetes, to better identify and understand the pathogenesis of the disease, more studies with a higher number of samples and more racial groups are needed. In the future, identifying the profile and locations of genetic susceptibility to gestational diabetes can be used in the patient's management.